2023
DOI: 10.2147/jir.s392350
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Ameliorates Type 2 Diabetes-Related Sarcopenia Through IL-33-Independent ILC2s/IL-13/STAT3 Signaling Pathway

Abstract: Purpose Sarcopenia has been described as a new complication of type 2 diabetes mellitus (T2DM). T2DM and sarcopenia impact each other, resulting in a variety of adverse outcomes such as frailty, disability, poor quality of life and increased mortality. Sodium butyrate (NaB) is reported to play a protective role against T2DM. The present study aimed to investigate whether NaB could ameliorate T2DM-related sarcopenia and the underlying mechanisms. Materials and Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…BA, one of the SCFAs, has been reported to have anti-inflammatory properties and may act as an energy source for muscle [57][58][59]. It has also been reported that administration of BA to an aged rat model increases muscle mass and fiber size, and the mechanism underlying the positive effects on muscle involves increased mTOR and inhibition of MuRF1 [60,61]. In addition, AA may benefit muscle function by improving glycogen replenishment and increasing acetyl-CoA concentrations in skeletal muscle [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…BA, one of the SCFAs, has been reported to have anti-inflammatory properties and may act as an energy source for muscle [57][58][59]. It has also been reported that administration of BA to an aged rat model increases muscle mass and fiber size, and the mechanism underlying the positive effects on muscle involves increased mTOR and inhibition of MuRF1 [60,61]. In addition, AA may benefit muscle function by improving glycogen replenishment and increasing acetyl-CoA concentrations in skeletal muscle [62,63].…”
Section: Discussionmentioning
confidence: 99%